Peran mediasi return on asset pada hubungan debt to equity ratio dan total asset turnover terhadap price to book value: Investigasi pada sektor Pertambangan Batu Bara - Muliyati, Muliyati; Mardiana, Fitra (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2021)
The purpose of this study is to explore the influence of debt to equity ratio (DER) and total asset turnover (TATO) on price to book value (PBV), and the role of return on assets (ROA) in mediating independent constructive relationships on dependents. The population in this study is as many as 24 Coal Mining companies, after being sorted based on sample criteria using purposive sampling techniques, there are 9 companies suitable to be sampled in this study. The analysis method used is Path Analysis by using SPSS version 21. The results of the study obtained that directly DER has no significant effect on ROA, while TATO has a significant effect on ROA. DER and TATO variables have no significant effect on PBV. While the results of indirect data analysis, ROA is not able to mediate the relationship between DER to PBV, and indirectly ROA is able to mediate the relationship between TATO to PBV.